2013
DOI: 10.1089/dia.2013.0108
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Longitudinal Study of the Impact of Sleeve Gastrectomy on Glycemic Control in Type 2 Diabetes Mellitus

Abstract: Laparoscopic sleeve surgery is a safe and effective treatment option among the obese Indian type 2 diabetes population with significant remission rates. Follow-up studies are necessary to assess the long-term durability of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The weight loss and percentage of EWL noted in one year were significantly reduced (31.14-7.8% and 61.52-15%, respectively). It was also found that anti-diabetic medication usage reduced from 88.57% to 11.4% [3].…”
Section: Short-term Effects Of Lsgmentioning
confidence: 90%
See 4 more Smart Citations
“…The weight loss and percentage of EWL noted in one year were significantly reduced (31.14-7.8% and 61.52-15%, respectively). It was also found that anti-diabetic medication usage reduced from 88.57% to 11.4% [3].…”
Section: Short-term Effects Of Lsgmentioning
confidence: 90%
“…The results showed that GB, LSG, and BPD change to decrease excess weight in patients by 47%, 62%, and 70%, respectively. While the reviews on LSG by Gill et al (2010) and Brethauer et al (2009) found that the mean percentage of loss was 47.3% and 60.4%, respectively [3].…”
Section: Different Types Of Surgeriesmentioning
confidence: 95%
See 3 more Smart Citations